(untitled) (Praxis Educativa, 2022)
In this research, perceptions of high school students on the rights of migrants have been identified and described. The sample consisted of 40 students from educational establishments in Greater Concepción-Chile. The methodology used was qualitative and the speeches of the students interviewed were analyzed in depth. The results indicate that they conceive immigration as a new phenomenon that they cannot explain clearly. Their speeches are contradictory because they show solidarity with immigrants but consider that prevent access to sources of work and that they cannot have the same rights as the national population.